Inflasi dan Suku Bunga terhadap Return Saham Subsektor Perbankan Indeks KOMPAS100 2015 – 2019 - Nanna Sugiyanto, Fransiskus Xaverius; Nazar, Shinta Ningtiyas; Syafrizal, Kansas (E-Jurnal Akuntansi, 2021)
The consider pointed to decide  &  to demonstrate experimentally the impact of swelling  &  intrigued rate on the stock return of the keeping money subsector stock within the KOMPAS100 record. Analyst utilized control factors, to be specific PER  &  PBV. This sort of investigate classified as quantitative inquire about  &  utilizing auxiliary information. The populace in this study are stocks within the KOMPAS100 record 2015-2019  &  utilized purposive testing strategy coming about 9 stocks of the keeping money subsector of KOMPAS100 list 2015-2019 as the test. The examination method utilized in this inquire about is numerous straight relapse. The comes about demonstrate that the expansion  &  intrigued rate factors at the same time impact stock return with PER  &  PBV as control factors. The expansion variable does not have a significant effect on stock returns. Intrigued rate variable incorporates a critical negative impact on stock returns. PER  &  PBV as control factors have no critical impact on stock return. Keywords: Inflation; Interests; Stock Return; Indeks KOMPAS100.